2017
DOI: 10.2320/jinstmet.j2017016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yttrium Addition on Plastic Deformation of Magnesium

Abstract: In this study, tensile tests of Mg-Y alloy single crystals and polycrystals were carried out to investigate influence of yttrium on activities of slip systems and a relationship between ductility of magnesium and active slip systems. Tensile directions of the single crystals and the polycrystals were parallel to (0001) and its rolling direction, respectively. Both tests were carried out at room temperature. Yield stress and ductility of Mg-(0.6-1.1) at%Y alloy single crystals were higher than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…19 indicate activation stress of FPCS in [11 20] calculated from CRSSs for FPCS of pure Mg 13) and Mg0.6 at%Y (0.6Y). 14) Activation stress of FPCS was found to be independent of yttrium addition, as shown in Fig. 19.…”
Section: A D V a N C E V I E Wmentioning
confidence: 87%
See 2 more Smart Citations
“…19 indicate activation stress of FPCS in [11 20] calculated from CRSSs for FPCS of pure Mg 13) and Mg0.6 at%Y (0.6Y). 14) Activation stress of FPCS was found to be independent of yttrium addition, as shown in Fig. 19.…”
Section: A D V a N C E V I E Wmentioning
confidence: 87%
“…Bending strain, ε (%) Bending strain, ε (%) Pure Mg [13] 0.6Y [14] Activation stress of FPCS Cracking point…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ando et al [4] have reported that pure magnesium single crystals deformed due to activation of second order pyramidal <c+a> slip in [112 � 0] tensile tests. On the other hand, Rikihisa et al [5] have reported that Mg-(0.6-1.1)at.%Y alloys deformed due to activation of first order pyramidal <c+a> slip in [112 � 0] tensile tests and showed high ductility at room temperature. However, the reason behind the change and activation of these slip systems have not been yet elucidated.…”
Section: Introductionmentioning
confidence: 99%